Steinhael's [Steinheil's] Galvanic Telegraph - Turnbull, Laurence (The Electro Magnetic Telegraph: with an Historical Account of its Rise, Progress, and Present Condition, 1853)
Diagram depicting various components of the galvanic telegraph system designed by German physicist, inventor, and engineer Carl August von Steinheil (1801-1870).
Keywords: Telegraph; Scientific apparatus and instruments; Scientific illustration; Communication; Communication and technology; Telecommunication; Electricity; Electric machines